Market withdrawals' of medicines in Germany after AMNOG: A comparison of HTA ratings and clinical guideline recommendations - Thomas R. Staab; Miriam Walter; Sonja Mariotti Nesurini; Charalabos-Markos Dintsios; Johann-Matthias von der Schulenburg; Volker E. Amelung; Jörg Ruoff (Health Economics Review, 2018)
Background: According to the AMNOG act, the German Federal Joint Committee (G-BA) determines the additional benefit of new medicines as a basis for subsequent price negotiations. Pharmaceutical companies may withdraw their medications from the market at any time during the process. This analysis aims to compare recommendations in clinical guidelines and HTA appraisals of medicines that were withdrawn from the German market since the introduction of AMNOG in 2011. Methods: Medications withdrawn from the German market between January 2011 and June 2016 following benefit assessment were categorized as opt-outs (max. 2 weeks after start of price negotiations) or supply terminations (during or after further price negotiations). Related guidelines were systematically analyzed. For all withdrawals, therapeutic area, additional benefit rating and recommendation status in relevant clinical guidelines were assessed. Results: Among 139 medications, 10 opt-outs and 12 supply terminations were identified. Twenty-one out of 22 withdrawn medicines (95%) received 'no additional benefit' appraisal by the G-BA (average 'no additional benefit' rating for all AMNOG products: 47%). Of the 22 medicines, 15 (68%) were recommended by at least one guideline at the time of benefit assessment and 18 (82%) on 1 June 2016. Heterogeneity among guidelines was high. Acceptance of clinical trial endpoints was different between G-BA appraisals and clinical guidelines. Conclusion: Our analysis revealed considerable differences across clinical guidelines as well as between clinical guidelines and HTA appraisals of the medicines that were withdrawn from the German market. Better alignment of the clinical perspective and close collaboration between all involved parties is required to achieve and maintain optimization of patient care.
Keywords: 330; AMNOG; Early benefit assessment; Product recalls and withdrawals; Opt-out